Table of Content - - (Journal of engineering sciences and information technology, 2023)
Table of Content: 1. Enhancing Coherent Optical Communication Performance Using FBG as Dispersion Compensator Eng. Raghad Mohammad Fayez Alalfi, Dr. Abdulkareem Alsalem 2. The role of modern augmented applications in improving the efficiency of engineering projects Eng. Sami Abdullah Mandani, Eng. Mohammad Jasem Alfareis 3. Development of a data encryption algorithm to enhance security in D2D communications by secure key exchange Eng. Essam Mohammad Asaad , Prof. Abdulkarim Assalem 4. Evaluation of Bus Rapid Transit System: Riyadh city, Saudi Arabia Ahmed Mohammed Alshehri 5. A GIS-Based Streets Network Analysis in Al-Riyadh District, Al-Khartoum City Dr. Sahar I. M. Abd Elrahman